Endogenous Determination of FDI Growth and Economic Growth:The OECD Case - Burcu Türkcan; I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2008)
This paper tests the endogenous relationship between FDI growth and economic growth using a panel dataset for 23 OECD countries for the period 1975-2004. In particular we estimate a two-equation simultaneous equation system with the generalized methods of moments (GMM) that treats economic growth and FDI growth as endogenous variables. We find that FDI growth and economic growth are significant determinants of each other. We also find that export growth rate and human capital are statistically significant determinants of both FDI growth and economic growth. Our findings lead us to conclude that FDI growth and economic growth have an endogenous relationship.
Keywords: C33; O5; F21; 330; FDI growth; economic growth; Panel Data; GMM; Auslandsinvestition; Wirtschaftswachstum; Momentenmethode; OECD-Staaten